Емоційний інтелект як чинник подолання стресу - Усик, К. М.; Usyk, K. M. (Габітус. - 2024. - Вип. 60. - С. 245-250, 2024)
Зазначено, що емоційний інтелект визначається як здатність особистості розпізнавати, розуміти та ефективно управляти власними та чужими емоціями. У статті проаналізовано вплив емоційного інтелекту на здатність особистості подолати стресові ситуації. Розглянуто сутність емоційного інтелекту та його компоненти: усвідомленість емоцій, регуляція емоцій, міжособистісні відносини тощо. Досліджено роль емоційного інтелекту у зменшенні рівня стресу та поліпшенні психологічного благополуччя.

Emotional intelligence is defined as a person’s ability to recognize, understand and effectively manage their own and other people’s emotions. The article analyzes the impact of emotional intelligence on a person’s ability to overcome stressful situations. On the basis of scientific research and theoretical concepts, the essence of emotional intelligence and its components are considered: awareness of emotions, regulation of emotions, interpersonal relations, etc. The authors of the article consider the role of emotional intelligence in reducing the level of stress and improving psychological well-being. It is noted that in modern realities, where stress becomes an indispensable component of everyday life, it is important to consider various aspects of psychological adaptation to it. Emotional intelligence, the ability to recognize, understand, and effectively manage one’s own and others’ emotions, is gaining more and more importance in this context. Emphasis is placed on identifying the concept of emotional intelligence as a separate construct due to the long-term observations of researchers that the life success of people is always related to the level of their cognitive abilities. Moreover, people with a high level of academic intelligence did not show significant success in various areas of life. The biological and social prerequisites of development are analyzed. Some researchers refer to the level of emotional intelligence of parents as biological. Social factors in the development of emotional intelligence include syntonia (the ability to feel the same emotional states that are characteristic of the immediate social environment).

Указано, что эмоциональный интеллект определяется как способность личности распознавать, понимать и эффективно управлять собственными и чужими эмоциями. В статье проанализировано влияние эмоционального интеллекта на способность личности преодолеть стрессовые ситуации. Рассмотрена сущность эмоционального интеллекта и его компоненты: осознанность эмоций, регуляция эмоций, межличностные отношения и т.д. Исследована роль эмоционального интеллекта в уменьшении уровня стресса и улучшении психологического благополучия.
Keywords: емоційний інтелект; соціальний інтелект; стрес; емоції; психологічна адаптація; emotional intelligence; social intelligence; stress; emotions; psychological adaptation; эмоциональный интеллект; социальный интеллект; стресс; эмоции; психологическая адаптация